Letter (copy) : Situation in Spain - McDonald, Florence
010-0106-001 EAB. International. 3rd September 1936. Miss F. E. McDonald, Royal Hotel, PLYMOUTH. Dear Miss McDonald, SITUATION IN SPAIN. The enclosed section of the report of the meeting of the three bodies held on Friday last to consider the situation in Spain, follows upon the reports of Sir Walter's statement to that meeting which I handed to you earlier in the week. In order that you might have the report in time for tomorrow's (Friday) meeting, only the principal speakers have been reported. Yours sincerely, International Department. Report. 292/946/10/114